2021
DOI: 10.3390/v13071242
|View full text |Cite
|
Sign up to set email alerts
|

Confound, Cause, or Cure: The Effect of Cannabinoids on HIV-Associated Neurological Sequelae

Abstract: The persistence of human immunodeficiency virus-1 (HIV)-associated neurocognitive disorders (HAND) in the era of effective antiretroviral therapy suggests that modern HIV neuropathogenesis is driven, at least in part, by mechanisms distinct from the viral life cycle. Identifying more subtle mechanisms is complicated by frequent comorbidities in HIV+ populations. One of the common confounds is substance abuse, with cannabis being the most frequently used psychoactive substance among people living with HIV. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 217 publications
(241 reference statements)
0
2
0
Order By: Relevance
“…Several studies have showed that HIV gp120 stimulates increased cortical fatty acid amide hydrolase (FAAH) [ 47 , 48 ], subsequently allowing for rapid 2-AG and AEA production [ 49 ], selective ligands for the NUCB1 linked to degree of depressive behavior [ 50 ], in the postsynaptic neuron, whereas decreased CNR1 expression promotes the release of 2-AG and AEA [ 51 , 52 ]. Herein, down-regulation of CNR1 expression and up-regulation of NUCB1 expression in neurons were found in the co-occurrence of depression disorder and SHIV infection, as detected by IHC and Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have showed that HIV gp120 stimulates increased cortical fatty acid amide hydrolase (FAAH) [ 47 , 48 ], subsequently allowing for rapid 2-AG and AEA production [ 49 ], selective ligands for the NUCB1 linked to degree of depressive behavior [ 50 ], in the postsynaptic neuron, whereas decreased CNR1 expression promotes the release of 2-AG and AEA [ 51 , 52 ]. Herein, down-regulation of CNR1 expression and up-regulation of NUCB1 expression in neurons were found in the co-occurrence of depression disorder and SHIV infection, as detected by IHC and Western blot.…”
Section: Discussionmentioning
confidence: 99%
“…Agonists of the CB2R have shown therapeutic potential against HIV-1 replication, neuroinflammation and neurotoxicity in several studies, which have been reviewed by different groups [ 50 , 51 , 52 , 53 , 54 , 55 ], and new supporting evidence continues to emerge [ 14 , 56 ]. In searching for strategies against CATB-induced neurotoxicity, we recently demonstrated that activating the CB2R with agonists decreases HIV-1 replication, CATB secretion, and neurotoxicity from HIV-infected macrophages [ 14 ].…”
Section: Introductionmentioning
confidence: 99%